151k views
4 votes
Drag each number to the correct location on the statements. Not all numbers will be used. Consider the sequence below. --3, -12, -48, -192, ... Complete the recursively-defined function to describe this sequence. f(1) =...... f(n) = f(n-1) × .....for n = 2, 3, 4... 3, 2, 3, 4, 12, -4

Drag each number to the correct location on the statements. Not all numbers will be-example-1

1 Answer

1 vote

ANSWER:

Explanation:

We have the following sequence:


-3,-12,-48,-192...

f(1), is the first term of the sequence, therefore, it would be:


f(1)=-3

Now, we calculate the common ratio, just like this:


\begin{gathered} r=(-192)/(-48)=4 \\ \\ r=(-48)/(-12)=4 \\ \\ r=(-12)/(-3)=4 \end{gathered}

So the sequence would be:


f(n)=f(n-1)\cdot4

Drag each number to the correct location on the statements. Not all numbers will be-example-1
User Superlee
by
5.2k points